Fotosyntesundervisning 2.0: Kraftfull kunskap och en vidgad syn på fotosyntesundervisning - Anders Eriksson; Niklas Gericke; Daniel Olsson (Dalarna university, 2023)
This article argues for a broader and more socially relevant photosynthesis instruction in compulsory science education. Presently, the predominant practice is traditional instruction, focusing on students' conceptual understanding of photosynthesis based on molecular and energy-related principles. Views of what is referred to as scientific literacy change in line with the new values and demands of a globalised society. Scientific literacy has evolved from a narrow conception of natural sciences to a broader teaching approach, addressing science from a whole society perspective. The article discusses how photosynthesis instruction can be redirected to future issues such as societal and sustainability and argues for a wider approach to scientific literacy involving active citizenship to address present and future sustainability challenges. A scientific literacy model is presented, along with its relation to the concept of powerful knowledge, defined as the kind of knowledge students need to have control and agency in their own lives. Powerful knowledge is discussed in terms of how photosynthesis instruction could be used to address societal and sustainability issues such as climate change, food chains, energy issues and food production. The need for a new and updated photosynthesis education 2.0 is presented.